Evaluasi Kepuasan Pengunjung sebagai Dasar Pengelolaan Lanskap di Kawasan Wisata Rammang-Rammang - Nurfaida; Wahyuni, Cri; Mantja, Katriani; Iswoyo, Hari; Dariati, Tigin; Dewi, Sinta (Jurnal Lanskap Indonesia, 2026)
The Rammang-Rammang Tourism Area is a leading destination with a unique karst landscape that attracts an increasing number of tourists every year. This condition makes it very important to evaluate visitor satisfaction to understand the tourist experience and improve the quality of sustainable landscape services. This study aims to formulate recommendations for landscape management strategies based on the results of visitor satisfaction evaluations in the Rammang-Rammang Tourism Area. The methods used include Importance Performance Analysis (IPA) to assess the level of importance and performance of various attributes, and Customer Satisfaction Index (CSI) to measure overall satisfaction levels. The IPA analysis results show that three attributes are the top priorities for improvement, ten attributes require improvement with low urgency, sixteen attributes need to be maintained, and one attribute can have its resources reallocated. The CSI value of 68.40% indicates that, in general, visitors are satisfied with their tourism experience. The findings of this study are important as a basis for decision-making in improving worship facilities, service standards, and visitor comfort support facilities, thereby strengthening the quality of the tourism experience and supporting sustainable landscape management in the Rammang-Rammang Tourism Area